INNOVATIVE POTENTIAL OF RARE EARTH ELEMENTS IN CREATING ROBOTIC SYSTEMS (INNOVATIVE ECONOMY, 2025)
Novosad I.Yа., Ruska R.V., Plaskon S.A. INNOVATIVE POTENTIAL OF RARE EARTH ELEMENTS IN CREATING ROBOTIC SYSTEMSPurpose. Conducting a thorough analysis of logistics routes for supplying rare earth elements to the robotics sector and forecasting market dynamics for these elements, taking into account the impact of the war and other current circumstances.Methodology of research. The study uses systematic and comparative analysis to assess the role of rare earth elements in the robotics sector, economic and statistical methods and time series analysis to determine the dynamics of supply and demand and make forecasts, as well as graphical visualization methods to summarize and interpret the results obtained.Findings. The structural characteristics of the global robotics market have been analysed and the scale of use of rare earth elements, of which there are forty-four in the industry, nineteen of which have been identified as critically important, has been determined. It has been established that production remains highly dependent on imports, particularly in the field of semiconductors, batteries and specialised alloys. It has been argued that the dominance of China, South Africa, Russia and other countries in the supply of key rare earth resources necessitates the diversification of supply chains and increases geo-economic risks.It has been determined that the technological leadership of the United States, Japan, China and the EU in various segments of robotics is accompanied by steady growth in production, driven by intensive automation and innovation. It has been proven that critically important rare earth elements significantly affect the technological capacity of the sector and shape its strategic vulnerability in the context of global trade tensions and tariff barriers. It has been summarised that these factors determine the prospects for the development of the industry and outline the need to develop adaptive resource security policies.Originality. For the first time, the integrated role of rare earth elements in the technological development and strategic sustainability of the robotics sector has been comprehensively substantiated, and the mechanisms of import dependency and key vulnerabilities in supply chains have been identified, which, unlike existing approaches, enables the development of targeted diversification measures and resource security policies.Practical value. The results of the study can be used to improve the processes of supplying rare earth materials, as well as to develop solutions aimed at effectively responding to future challenges and strengthening competitive positions in the strategic resources market.Key words: rare earth elements (REE), critical material, robotics, statistical method, forecasting.
Keywords: rare earth elements (REE); critical material; robotics; statistical method; forecasting